Lighting and performance: an analysis on lighting efficiency of architecture studio / Fazidah Hanim Husain - Fazidah Hanim, Husain (Universiti Teknologi MARA, Perak, 2016)
Lighting is one of the key elements in any space and building infrastructure. Good design for an area in the building requires sufficient light that contributes to the efficiency of the activities. The correct method allows natural light to transmit, reduce heat and glare in providing a conducive earning environment. Light plays a significant influence to the quality of space and contributes focus of the students in an architecture studio. Previous research has shown that the effect of light also controlled emotions, behavior, and mood of the students. The operations of artificial lighting that have been used most of the time in an architecture studio during day and night may create lavishness and inadequacy at the same time. Therefore, this paper focuses on the identifying the quality of light for the architecture studio in UiTM (Perak), to instill a creative learning environment. Several methodologies adopted in this study such as illuminance level measurement using lux meter (LM-8100), and a questionnaire survey in gauging the lighting comfort level from students’ perspective. The study revealed that the illuminance level in the architecture studio is insufficient and not in the acceptable range stated in the Malaysian: Standards 1525:2007 and not evenly distributed. The study also concluded that the current studio environment is not conducive and appears monotonous.